2006
DOI: 10.1152/ajprenal.00123.2006
|View full text |Cite
|
Sign up to set email alerts
|

Nature of glomerular capillary permeability changes following acute renal ischemia-reperfusion injury in rats

Abstract: This study was performed to evaluate the alterations of glomerular filtration barrier characteristics following acute renal ischemia-reperfusion (I/R). Ischemia was induced in anesthetized rats by unilateral renal artery occlusion for either 20 or 60 min, followed by reperfusion during 20 or 60 min, respectively, with the contralateral kidney serving as control. Sieving coefficients (theta) were obtained by analyzing Ficoll [mol.radius (a(e)) 13-85 A] in urine and plasma after 20 and 60 min I/R. Furthermore, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
83
2
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(92 citation statements)
references
References 32 publications
6
83
2
1
Order By: Relevance
“…The to high-MW Ficolls (mol. radius Ͼ50 Å ) in sham animals in vivo in this experimental setting are extremely low and comparable to the fractional clearance of proteins of equivalent size (24,25). Sham animals for the ENDO groups (SHAM-120; n ϭ 7) received 120 min of constant NaCl infusion, 10 ml ⅐ kg Ϫ1 ⅐ h Ϫ1 , and, matching (in time) the infusion of LPS in the ENDO groups, a sham infusion of an extra 200 l NaCl during 30 min.…”
Section: Methodsmentioning
confidence: 89%
See 2 more Smart Citations
“…The to high-MW Ficolls (mol. radius Ͼ50 Å ) in sham animals in vivo in this experimental setting are extremely low and comparable to the fractional clearance of proteins of equivalent size (24,25). Sham animals for the ENDO groups (SHAM-120; n ϭ 7) received 120 min of constant NaCl infusion, 10 ml ⅐ kg Ϫ1 ⅐ h Ϫ1 , and, matching (in time) the infusion of LPS in the ENDO groups, a sham infusion of an extra 200 l NaCl during 30 min.…”
Section: Methodsmentioning
confidence: 89%
“…Sham animals for the ANA-5 group (SHAM-5; n ϭ 8) obtained a bolus of NaCl (250 l) 5 min before the Ficoll sieving assessment. Because there were no indications of changes in glomerular permeability between 5 and 120 min in the sham animals in the present experiments, nor in control rats in previous studies (24,25), we employed the glomerular sieving curves for the SHAM-120 animals as control curves for the ENDO-(60)/90 groups and those for SHAM-5 as controls for the ANA-40 group. In all sham groups, FITC-Ficoll (70/400) was infused intravenously using a protocol identical to those in the experimental groups.…”
Section: Methodsmentioning
confidence: 95%
See 1 more Smart Citation
“…Albumin permeability was not assessed due to high levels of denatured protein and free iodine ( 125 I) in all our current albumin preparations, leading to marked overestimations of the apparent for albumin. However, we have in previous experiments shown a near-complete coupling between alterations in for albumin and for high-molecular-weight Ficoll (50 -80Å) when glomerular permeability has been altered (3,9,46,47). Thus for Ficoll 50 -80Å seems to function as a good surrogate marker for glomerular albumin permeability across the GFB.…”
mentioning
confidence: 75%
“…Sutton et al (43) demonstrated endothelial injury, cytoskeletal alteration, impaired cell-cell adhesion, and leakage of dextran from the renal microvasculature into the interstitium after bilateral renal pedicle occlusion (43). Using a rat renal pedicle occlusion model, Rippe et al (37) reported that renal permeability to Ficoll was increased by 60 min of unilateral renal ischemia, primarily large (Ͼ55 Å) Ficoll molecules. However, Andersson et al (2) found damage to both the size and charge barriers after mild (15 min) ischemia in isolated, perfused rat kidneys without morphological change as assessed by electron microscopy, suggesting that the glycocalyx (an endothelium-derived structure not imaged by electron microscopy) might be the source of barrier damage from ischemia.…”
Section: Discussionmentioning
confidence: 99%